2020
DOI: 10.1177/0961203320928409
|View full text |Cite
|
Sign up to set email alerts
|

Ocular flare-up in patients with systemic lupus erythematosus following discontinuation of hydroxychloroquine

Abstract: In this report, we describe two patients with systemic lupus erythematosus (SLE) who manifested with posterior segment flare-up approximately three months after cessation of hydroxychloroquine (HCQ). They were stable systemically with no history of hypertension or nephropathy at the time of referral. Our first patient presented with bilateral retinal vein occlusion, while evidence of choroidal involvement such as vascular leakage and wedge-shaped filling delay was present in indocyanine green angiography of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moschos et al reported that visual acuity and mfERG scores improved in 42 SLE patients after the cessation of hydroxychloroquine therapy [199]. On the other hand, posterior segment flare-ups have been reported after stopping hydroxychloroquine [200]. Steroidal systemic drugs like prednisolone used in acute phases of the disease are often tapered off and substituted with an immunosuppressant depending on the presentation of the disease [93].…”
Section: Management and Treatmentmentioning
confidence: 99%
“…Moschos et al reported that visual acuity and mfERG scores improved in 42 SLE patients after the cessation of hydroxychloroquine therapy [199]. On the other hand, posterior segment flare-ups have been reported after stopping hydroxychloroquine [200]. Steroidal systemic drugs like prednisolone used in acute phases of the disease are often tapered off and substituted with an immunosuppressant depending on the presentation of the disease [93].…”
Section: Management and Treatmentmentioning
confidence: 99%